en - Putu Wahyu Wismarini (Program Magister Linguistik Universitas Udayana, 2021)
In this research was examined about perlocution meaning of teacher’s speech acts during English learning processes in VI grade at institute courses Hallo English Course. There are three methods which use in this research that is, method of collecting data which doing by non-participants observation, the method of analyzing data which use frontier method i.e. pragmatics method which is use speech participant as determinant device from the identity of object research and the method of presentations of the analyzing data in this research. The speech acts which is build in English learning processes is a speech acts of speech. In terms of meaning of speech act there are three meaning that is locution speech acts, the meaning of illocution speech acts, and perlocution speech acts. Some speech which contained by perlocution found in this research, one of government effect which found in teacher’s speech data to the one of student like in the example “Abel count your friends please!” ‘Abel tolong hitung teman-temanmu!’ is a meaning of perlocution speech acts which has government effects.